Montaigne, czyli o wielkości małych słów - Ryczek, Wojciech (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The main aim of this paper is to propose a new Polish translation one of the well-known Michel de Montaigne’s essays, De la vanité des paroles (On the Vanity of Words, I 51). For the humanist, rhetoric delimited only to elocution responsible for linguistic adornments becomes the subject for critical investigation. In a short introduction to the essay, the author takes into consideration the rhetoric of Montaigne’s discourse on ‘the vanity of words’ with a particular attention to two rhetorical forms: amplification and figuration. Raising questions about lack of temperance in amplifying and adorning words with tropes and figures, the humanist attempted to revalorize linguistic and stylistic simplicity. Therefore, to find the proper words for various things, emotions and experiences are the central concern of an essay, a new literary genre invented by Montaigne.